Managing knowledge in project environments - Payne, Judy; Roden, Eileen; Simister, Stephen J. (Fundamentals of project management., 2019)
Managing Knowledge in Project Environments illustrates how knowledge management (KM) contributes to successful project work. KM is widely practised in project environments, but managers don't always recognise the knowledge aspects of their work and tend to treat KM as a series of specific activities rather than a way of making project work produce better outcomes in different contexts. To overcome this challenge, the authors present KM as an integral part of project work and explain it using principles: KM fundamentals that apply anywhere. A series of context factors provides readers with a framework for understanding and thinking about what KM means for their context: their goals, their projects, their organisations and their working environments. Hidden KM is exposed, myths are debunked and practical guidance explains how to build KM into projects and portfolios. The approach is consistent with current guidance including the BSISO management systems standard for KM and the seventh edition of APM's 'Body of knowledge'. The aim is to help project professionals, sponsors, PMO members and others who can make a difference manage knowledge more effectively in project environments. Managing Knowledge in Project Environments offers everyone involved in project work a definitive short guide to the subject.